A Japanese constellation Toyo Ito, Kazuyo Sejima, SANAA, Ryue Nishizawa, Sou Fujimoto, Akihisa Hirata, Junya Ishigami - Gadanho, Pedro 1968-; Resnick, Sarah (The Museum of Modern Art, 2016)
Published in conjunction with an exhibition at The Museum of Modern Art, A Japanese Constellation focuses on the work of a small group of architects and designers influenced by and gravitating around the architect Toyo Ito and the architectural firm SANAA. Beginning with an overview of Ito's career and his influence as a mentor to a new generation of Japanese architects, the catalogue presents a richly illustrated portfolio of recent works by three generations of internationally acclaimed designers, including Sou Fujimoto, Akihisa Hirata and Junya Ishigami. A Japanese Constellation reveals a network of influence and cross-pollination that has become particularly relevant at the start of the 21st century. Essays by curators, architectural historians and critics reflect on the transmission of an architectural sensibility, and suggest an alternative model to what has been commonly described as an individuality-based "star-system" in architecture. Offering a panorama of interlinked, settled or up-and-coming stars, the publication reveals how shared architectural themes travel across generations of architects, creating a strong identity for a regional practice with global impact
Published in conjunction with the exhibition 'A Japanese Constellation: Toyo Ito, SANAA, and Beyond', at The Museum of Modern Art, New York, March 13-July 4, 2016. Organized by Pedro Gadanho, Director, Museum of Art, Architecture and Technology, Lisbon, with Phoebe Springstubb, Curatorial Assistant, Department of Architecture and Design, The Museum of Modern Art
Keywords: Ito, Toyo; Sejima, Kazuyo; Nishizawa, Ryue; Fujimoto, Sou; Hirata, Akihisa; Ishigami, Junya; SANAA; Geschichte 1990-2016; Architektur; Japan; Ausstellungskatalog -- Museum of Modern Art -- 13.03.2016-04.07.2016 -- New York, NY